Illuminating waveguide - Cheng, Pamela Jia En (Nanyang Technological University, 2020)
Optical waveguides are usually performed as a light pipe to guide light along the waveguide. They are used in a variety of applications such as computer networking, broadcasting, telecommunications, and performing strain measurements in buildings.